2018
DOI: 10.1186/s12938-018-0516-2
|View full text |Cite
|
Sign up to set email alerts
|

Translation of robot-assisted rehabilitation to clinical service: a comparison of the rehabilitation effectiveness of EMG-driven robot hand assisted upper limb training in practical clinical service and in clinical trial with laboratory configuration for chronic stroke

Abstract: BackgroundRehabilitation robots can provide intensive physical training after stroke. However, variations of the rehabilitation effects in translation from well-controlled research studies to clinical services have not been well evaluated yet. This study aims to compare the rehabilitation effects of the upper limb training by an electromyography (EMG)-driven robotic hand achieved in a well-controlled research environment and in a practical clinical service.MethodsIt was a non-randomized controlled trial, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…A recent study with Amadeo reported gains in the 9-hole Peg test, when subjects received the robotic training after a 3 hour session of physiotherapy that included 45 min of occupational therapy and 45 min of biomechanical training of upper and lower limbs. 34 Several other studies have used wearable hand robots (X-Glove 31 , VAEDA 32 , Hand-of-Hope 35,36 , HandSOME 59 ) that enabled practice of reach, grasp and release tasks with robotic assistance to hand movement. All of these studies reporting signi cant gains on a variety of functional scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study with Amadeo reported gains in the 9-hole Peg test, when subjects received the robotic training after a 3 hour session of physiotherapy that included 45 min of occupational therapy and 45 min of biomechanical training of upper and lower limbs. 34 Several other studies have used wearable hand robots (X-Glove 31 , VAEDA 32 , Hand-of-Hope 35,36 , HandSOME 59 ) that enabled practice of reach, grasp and release tasks with robotic assistance to hand movement. All of these studies reporting signi cant gains on a variety of functional scales.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials with this robot have shown signi cant impairment reductions and functional gains in chronic stroke subjects. 35,36 The FINGER robot provides assistance to the index and middle ngers as the subject plays a video game that simulates playing a guitar. A clinical trial reported signi cant gains in several clinical scales, with authors noting that subjects with impaired proprioception bene ted less from the training.…”
Section: Introductionmentioning
confidence: 99%
“…Powered hand exoskeletons that can be integrated into ADL practice have shown success in improving hand function of stroke patients [11][12][13][14]. However the electronics, motors or pneumatic power sources of these devices result in increased weight, complexity and cost.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in different studies that different movement types can be classified from EMG activity from the muscles in the affected limb. These movements include finger movements [14], various functional hand movements, such as open/close [15,[19][20][21][22] and grasps [23], wrist extension [16], elbow and shoulder movements [24], and reaching [25]. Some of the techniques that have been used for decoding the attempted movements from the EMG are amplitude thresholds of the EMG signal envelope and proportional control [14,20], and pattern recognition approaches using, e.g., Hudgins time-domain features [15], autoregressive coefficients [22], empirical mode decomposition [26], and wavelets [27].…”
Section: Introductionmentioning
confidence: 99%